Parathyroid hormone levels after parathyroidectomy for secondary hyperparathyroidism - Nascimento Junior,Climério Pereira (2021)
SUMMARY OBJECTIVE: The parathormone level after parathyroidectomy in dialysis patients are of interest. Low levels may require cryopreserved tissue implantation; however, the resection is necessary in case of recurrence. We analyzed post parathyroidectomy parathormone levels in renal hyperparathyroidism. METHODS: Prospective observation of postoperative parathormone levels over defined periods in a cohort of dialysis patients that underwent total parathyroidectomy and immediate forearm autograft from 2008 to 2010, at a single tertiary care hospital. RESULTS: Of 33 patients, parathormone levels until 36 months could be divided into four patterns. Patients with stable function (Pattern 1) show relatively constant levels after two months (67% of the cases). Early function and later failure (Pattern 2) were an initial function with marked parathormone reduction before one year (18%). Graft recurrence (Pattern 3) showed a progressive increase of parathormone in four cases (12%). Complete graft failure (Pattern 4) was a nonfunctioning implant at any period, which was observed in one patient (3%). Parathormone levels of Pattern 3 became statistically different of Pattern 1 at 36 months. CONCLUSIONS: Patients that underwent the total parathyroidectomy and autograft present four different graft function patterns with a possible varied therapeutic management.